Epidermal Growth Factor Receptor and Ki-67 Expression in Canine Gliomas. (November 2016) - Fraser, A. R.; Bacci, B.; le Chevoir, M. A.; Long, S. N.
Novel therapies, including molecular targeted therapies, are being developed for the treatment of human gliomas. To use such therapies for canine gliomas, more complete characterization of molecular targets is required. Epidermal growth factor receptor (EGFR) is one such therapeutic target used in human glioma trials, and the Ki-67 labeling index (LI) is a marker of proliferation and a prognostic indicator. The objectives of this cross-sectional study were to evaluate the expression of EGFR and Ki-67 in canine gliomas and to determine if immunopositivity is associated with tumor type and histologic grade. Thirty-one formalin-fixed, paraffin-embedded canine gliomas were evaluated for EGFR and Ki-67 expression by immunohistochemistry. EGFR immunopositivity was evaluated using a semi-quantitative score and the Ki-67 LI calculated based on the percentage of positive cells. EGFR and Ki-67 expression were identified in 16 of 31 (52%) and 28 of 31 (90%) tumors, respectively. EGFR expression was significantly greater in high-grade tumors compared with low-grade tumors ( P = .04) and was significantly greater in gliomatosis cerebri compared with oligodendroglioma ( P = .002), astrocytoma ( P = .01), and oligoastrocytoma ( P = .04). The Ki-67 LI was significantly greater in high-grade tumors compared with low grade tumors ( P = .02); the median Ki-67 LI was 2.3% (range, 0%–17.6%) for low-grade tumors and 9.3% (range, 1.7%–41.0%) for high-grade tumors. A significant moderate correlation was identified between EGFR immunopositivity and Ki-67 LI ( r = 0.47, P = .007). Overall, EGFR may be a suitable therapeutic target for some canine gliomas, particularly gliomatosis cerebri.